2018
DOI: 10.1589/jpts.30.832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active vibration exercise using a Flexi-Bar on balance and gait in patients with chronic stroke

Abstract: [Purpose] This study aimed to investigate the effect of active vibration exercise using a Flexi-Bar on the balance and gait of chronic stroke patients. [Subjects and Methods] Twenty-two patients with chronic stroke were randomly assigned to an experimental or control group (n=11 each). The experimental group performed active vibration exercise using a Flexi-Bar. Balance was measured using the Berg Balance Scale and Functional Reach Test. Gait was measured with the 10-meter Walk Test and Timed Up and Go Test. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Two studies have investigated the effects of flexi-bar training on the physical performance in the older population. 21 22 The authors reported that the performance in TUG and 10MWT was improved after long-term flexi-bar training. 21 However, these studies had no placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies have investigated the effects of flexi-bar training on the physical performance in the older population. 21 22 The authors reported that the performance in TUG and 10MWT was improved after long-term flexi-bar training. 21 However, these studies had no placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…21 22 The authors reported that the performance in TUG and 10MWT was improved after long-term flexi-bar training. 21 However, these studies had no placebo group. Thus, drawing a conclusion from these two studies is inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations